EVALUATING AND UNDERSTANDING THE TOURIST EXPERIENCE: AN EMPIRICAL STUDY IN JAMMU AND KASHMIR - Ramjit, S. (ENLIGHTENING TOURISM. A PATHMAKING JOURNAL)
The aim of the present study is to identify and understand the tourist experience construct, and how it differs by their age, sex, income level, education and to suggest and recommend the strategies to develop the Jammu and Kashmir as a tourist destination and enhance its brand image. The study was carried out by collecting relevant information from secondary data sources, which included books, journals and reports published by government of India, Government of Jammu and Kashmir. A self structured Questionnaire was designed and distributed among the domestic and international tourists who visited Jammu & Kashmir. The sample size was 291 and the study was conducted in the whole state of Jammu and Kashmir. Data analysis was done by applying factor analysis, and descriptive statistics. There were five factors those constituted the tourist experience like ’’Transportation and Service by the different Carriers’, ’Services at the Destination’, ’Hotels and restaurants’, ’Infrastructure at the destination’ and Safety Security and Crowd Management’ and out of these the first two leaves the implications for further improving and developing the destinations in Jammu and Kashmir. The outcomes of the study as whole have significant managerial implications for destination marketing managers.